Perceptions of health-related quality of life among adults living with sickle cell disease in Cape Town, South Africa - Ingram, Clair (Division of Human Genetics, 2018)
Sickle cell disease (SCD) is a chronic, heritable blood disorder with affected individuals suffering from debilitating health issues and requiring frequent hospitalisation. SCD is highly prevalent in areas of the world where malaria is endemic and specifically in Sub-Saharan African (SSA) region from where a number of migrants flee to South Africa. This has resulted in increased numbers of SCD patients in the South African healthcare system requiring holistic treatment and care, and ultimately improvement of their health-related quality of life (HRQL). There is limited empirical information on issues related to HRQL in SCD in Africa, with none available on adults living with SCD in South Africa. For this reason, this study was carried out with the aim of qualitatively exploring the perceptions of HRQL in adult SCD patients at Groote Schuur Hospital in Cape Town. Participants were selected from Groote Schuur Hospital, a tertiary referral hospital in Cape Town, South Africa using a purposive sampling method. Participants were asked about how their condition affected physical and psychological functioning, effects of their health on relationships and social issues such as education and employment opportunities as well as discrimination. Perceptions of access to and satisfaction with healthcare, coping strategies and independent living skills were also explored. The data collected for this study were analysed using the framework approach and thematic content analyses methods. Results suggest that participants believed their functioning was affected by the constant and unpredictable nature of SCD clinical events, and this was seen to have social, financial and psychological implications. Environmental factors such as weather, activity and psychological state had significant impact on participants' health, with pain being a common complication of the condition often making coping with the condition difficult. Participants also experienced health-related discrimination and stigma in personal and social relationships and within the workplace often with negative emotional consequences. Both the positive and negative experiences with healthcare were also described. Participants found ways to cope with their condition but it appeared that SCD had more of a negative overall impact on various domains of HRQL for participants. Insights in to the impact of SCD on adult patients is important to allow for healthcare professionals to better understand patient needs and to implement more effective coping and self-management strategies appropriate for their patients. It also allows for genetic counselling services to be better tailored to addressing the concerns and needs of patients to provide better educational and psychosocial support.